Changes in hydration, body-cell mass and endurance performance of professional soccer players through a competitive season - Mascherini, G.; Gatterer, H.; Lukaski, H.; Burtscher, M.; Galanti, G. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of this paper was to determine changes of the bioelectrical impedance vector (BIVA) throughout a soccer season and to ascertain whether vector changes are associated with endurance performance changes.